2016
DOI: 10.1001/jamaoto.2015.2607
|View full text |Cite
|
Sign up to set email alerts
|

Use of18F-Fludeoxyglucose–Positron Emission Tomography/Computed Tomography for Patient Management and Outcome in Oropharyngeal Squamous Cell Carcinoma

Abstract: 18F-fludeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) has been performed widely in diagnosis and management of patients with oropharyngeal squamous cell carcinoma (OPSCC). This review summarizes the literature on this tool in the management of these patients. The use of FDG-PET/CT helps in accurate staging of primary tumor, nodal involvement, and distant metastasis of patients with OPSCC. Contrast-enhanced FDG-PET/CT combines high-resolution CT and functional FDG-PET, providing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Positron-emission tomography (PET) with 18 F-fluorodeoxyglucose (FDG) depicts the tumor metabolic rate of glucose. The tumor metabolic rate is one of the important factors that reflect tumor aggressiveness, and thus the determination of a tumor’s FDG uptake has been reported to improve the accuracy of the diagnosis, staging, and detection of recurrence in HNSCCs [1, 2]. The TBF has also been reported to reflect tumor characteristics such as tumor neo-angiogenesis, and has thus been found to be useful for the pretreatment assessments of patients' need for chemoradiotherapy, and for therapeutic monitoring [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Positron-emission tomography (PET) with 18 F-fluorodeoxyglucose (FDG) depicts the tumor metabolic rate of glucose. The tumor metabolic rate is one of the important factors that reflect tumor aggressiveness, and thus the determination of a tumor’s FDG uptake has been reported to improve the accuracy of the diagnosis, staging, and detection of recurrence in HNSCCs [1, 2]. The TBF has also been reported to reflect tumor characteristics such as tumor neo-angiogenesis, and has thus been found to be useful for the pretreatment assessments of patients' need for chemoradiotherapy, and for therapeutic monitoring [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…After treatment of OPSCC with surgical resection, chemotherapy or radiation therapy, changes in the normal tissue and anatomy (edema, hyperemia, and fibrosis) may affect the accuracy of imaging modalities in detecting residual disease[1]. Therapy assessment is an important step in the management of patients with OPSCC; since accurate confirmation of complete response can lead to discontinuing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, ultrasound (US) MRI and PET/CT were evaluated in detection of neck residual disease in patients with OPSCC and concluded that PET/CT combined with neck US could be a reliable and cost effective strategy in this setting [36]. In term of CT scan, neck CECT scans could not differentiate between the residual disease and therapy related changes such as necrotic and scar tissue [1,37]. Finally, dental repair materials, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of 18 F-FDG PET/CT imaging in initial staging, therapy planning, and therapy assessment of different cancers has been well established (14)(15)(16)(17)(18)(19)(20). Multiple studies claimed that follow-up 18 F-FDG PET/CT scanning is valuable when there is a clinical suspicion of disease recurrence.…”
Section: Discussionmentioning
confidence: 99%